Comparison of efficacy of butorphanol and nalbuphine as premedicant in patients undergoing elective craniotomy using propofol and desflurane anesthesia – A randomized clinical study - Pal, Tanaya; Biswas, Chaitali; Bhar Kundu, Sudeshna (Asian Journal of Medical Sciences, 2022)
Background: Long duration neurosurgical procedures require the use a relatively longer acting analgesic which will give equianalgesia like a short-acting opioid without needing repeated administration or an infusion. Aims and Objectives: In this study, we investigated and compared the intraoperative analgesic efficacy and post-operative recovery outcome of intravenous (IV) butorphanol and IV nalbuphine in non-emergency craniotomy patients. Materials and Methods: A prospective, randomized, and double-blind study was conducted involving 60 patients of age 18–50 years, randomly assigned into two equal groups receiving either 1 mg butorphanol IV (Group B) or 10 mg nalbuphine IV (Group N) 10 min before induction of general anesthesia. Patients were monitored for changes in blood pressure, heart rate (HR) perioperatively and duration of analgesia, and Ramsay Sedation Score (RSS) postoperatively. The results were recorded and analyzed statistically using Pearson’s Chi-square test for Independence of Attributes/Fisher’s Exact Test and Student’s t-test for continuous variables. Results: Statistically significant fall in HR and mean blood pressure was seen in both groups during intraoperative period, though fall was more in the nalbuphine group. Duration of analgesia was statistically significant in Group B than Group N (249.27±18.33 vs. 240.13±15.70, P=0.043). Sedation was more with nalbuphine as time to achieve RSS 2 was less with butorphanol. Conclusion: Inj. butorphanol and inj nalbuphine both showed satisfactory result in maintaining hemodynamic stability and long duration of analgesia. When compared, butorphanol provided longer duration of analgesia and less post-operative sedation.